Melatonin Enhances the Tolerance and Recovery Mechanisms in Brassica juncea (L.) Czern. Under Saline Conditions - Park, Hee-Soon; Kazerooni, Elham Ahmed; Kang, Sang-Mo; Al-Sadi, Abdullah Mohammed; Lee, In-Jung (Frontiers in Plant Science, 2021)
Melatonin has been recently known to stimulate plant growth and induce protective responses against different abiotic stresses. However, the mechanisms behind exogenous melatonin pretreatment and restoration of plant vigor from salinity stress are remain poorly understood. The present study aimed to understand the effects of exogenous melatonin pretreatment on salinity-damaged green mustard (Brassica juncea L. Czern.) seedlings in terms of oxidative stress regulation and endogenous phytohormone production. Screening of several melatonin concentrations (0, 0.1, 1, 5, and 10 μM) on mustard growth showed that 1 μM concentration revealed an ameliorative increase of plant height, leaf length, and leaf width. The second study aimed at determining how melatonin application can recover salinity-damaged plants and studying its effects on physiologic and biochemical parameters. Under controlled environment conditions, mustard seedlings were irrigated with distilled water or 150 mM NaCl for 7 d. This was followed by 1μM melatonin application to determine its recovery impact on the damaged plants. Furthermore, several physiologic and biochemical parameters were examined in stressed and unstressed seedlings with or without melatonin application. Our results showed that plant height, leaf length/width, and stem diameter were enhanced in 38-day-old salinity-stressed plants under melatonin treatment. Melatonin application obviously attenuated salinity-induced reduction in gas exchange parameters, relative water content, and amino acid and protein levels, as well as antioxidant enzymes, such as superoxide dismutase and catalase. H2O2 accumulation in salinity-damaged plants was reduced by melatonin treatment. A decline in abscisic acid content and an increase in salicylic acid content were observed in salinity-damaged seedlings supplemented with melatonin. Additionally, chlorophyll content decreased during the recovery period in salinity-damaged plants by melatonin treatment. This study highlighted, for the first time, the recovery impact of melatonin on salinity-damaged green mustard seedlings. It demonstrated that exogenous melatonin supplementation significantly improved the physiologic and biochemical parameters in salinity-damaged green mustard seedlings.